Effects of rearing tank colour on growth indices, blood chemistry, digestive enzymes, expression of stress and growth‐related genes of Asian sea bass juvenile (Lates calcarifer). (25th April 2022) - Morshedi, Vahid; Pradhoshini, Kumara Perumal; Tangestani, Narjes; Ghasemi, Ahmad; Sotoudeh, Ebrahim; Gamoori, Reza; Musthafa, Mohamed Saiyad
Abstract: The background colour of the fibreglass tanks attributed to their significant correlation with light intensity and spectrum serves as one of the major factors influencing growth performance and stress levels of cultured fish. Moreover, it plays a key role in the successful production of the cultured species, which is challenging under confinement conditions. On the other hand, Asian sea bass ( Lates calcarifer ) has received significant attention among researchers due to its high‐profit value and growing demand in the global market. Hence, the current study was designed to investigate the effects of different tank background colours (white, red, black and blue) on growth indices, body composition, digestive enzymes, haematological parameters, expression of stress and growth‐related factors in L. calcarifer . Therefore, fish (160.90 ± 6.0 g) were distributed into 12 fibreglass tanks (250‐L) including four treatments in triplicates and were reared for 6 weeks. According to the present results, the highest specific growth rate was observed in fish raised in red‐coloured tank followed by white and black tanks. Maximum weight gain (WG) and high protein efficiency ratio (PER) were observed in fish raised in red‐coloured tank followed by white‐, black‐ and blue‐coloured tanks, respectively. Modulation of the main digestive enzymes was observed across four treatments indicating different strategies for the utilization of nutrients by fish. Fish from red‐ and white‐coloured tanks showed a lower level of cortisol and higher levels of heat shock protein (HSP70) when compared to the other groups. The present findings indicate that red colour is the most suitable background colour for rearing Asian sea bass juveniles followed by white colour compared with the other ones.